Purification of green fluorescent protein using fast centrifugal partition chromatography - Soares, Bruna P.; Santos, João H.P.M.; Martins, Margarida; Almeida, Mafalda R.; Santos, Nathalia V. [UNESP]; Freire, Mara G.; Santos-Ebinuma, Valéria C. [UNESP]; Coutinho, João A.P.; Pereira, Jorge F.B. [UNESP]; Ventura, Sónia P.M. (Elsevier, 2021)
The green fluorescent protein (GFP) is a biomolecule used in many biological applications such as biomarkers and biosensors, which require high purity levels. It is usually obtained from recombinant Escherichia coli strains, which also produces other endogenous proteins, demanding multiple purification steps, and consequently, increasing the overall costs to obtain pure GFP. Simpler and cheaper purification methods like Aqueous Biphasic Systems (ABS) were already successfully applied to purify GFP at lab scale. Therefore, the development of automatized industrially compatible purification platforms, such as countercurrent chromatography using ABS, can potentially improve the GFP production. This work studied the continuous purification of the variant enhanced GFP (EGFP) by applying ABS composed of polyethylene glycol (PEG 8000), sodium polyacrylate (NaPA 8000) and sodium sulfate (Na2SO4) as electrolyte. An initial screening was carried by changing the electrolyte content in the ABS. The increase of this condition has demonstrated an increase on the EGFP partition for the PEG-rich phase. The most efficient ABS and, at the same time, with the most appropriate conditions, namely the system composed of 15 wt% PEG 8000 + 4.5 wt% NaPA 8000 + 2.5 wt% Na2SO4 was chosen and applied on the fast centrifugal partition chromatography (FCPC). After optimization, the best operational conditions were identified, i.e. a flow rate of 2.5 mL.min−1 and rotation speed of 2000 rpm at ascending mode, and the best results obtained, meaning a purification of 89.93% and a recovery yield of 82.3%, confirming the potential of FCPC to the continuous purification of EGFP.
Keywords: Aqueous biphasic systems; Electrolyte; Enhanced green fluorescent protein; Fast centrifugal partition chromatography; Purification